Validation of MicroRNA-188-5p Inhibition Power on Tumor Cell Proliferation in Papillary Thyroid Carcinoma. (15th May 2020) - Zhou, Ping; Irving, Andrew; Wu, Huifang; Luo, Juan; Aguirre, Johana; Costa, Mariana; Khamsuree, Monny; Gerads, Natascha; Liu, Weibang
Given the crucial role of microRNAs in the cellular proliferation of various types of cancers, we aimed to analyze the expression and function of a cellular proliferation-associated miR-188-5p in papillary thyroid carcinoma (PTC). Here we demonstrate that miR-188-5p is downregulated in PTC tumor tissues compared with the associated noncancerous tissues. We also validate that the miR-188-5p overexpression suppressed the PTC cancer cell proliferation. In addition, fibroblast growth factor 5 (FGF5) is observed to be downregulated in the PTC tumor tissues compared with the associated noncancerous tissues. Subsequently, FGF5 is identified as the direct functional target of miR-188-5p. Moreover, the silencing of FGF5 was found to inhibit PTC cell proliferation, which is the same pattern as miR-188-5p overexpression. These results suggest that miR-188-5p-associated silencing of FGF5 inhibits tumor cell proliferation in PTC. It also highlights the importance of further evaluating miR-188-5p as a potential biomarker and therapy target in PTC.